Factors associated with breast cancer screening behaviors in a sample of Jamaican women in 2013. Issue 9 (20th October 2020) - Balas, Nora; Yun, Huifeng; Jaeger, Byron C; Aung, Maung; Jolly, Pauline E
ABSTRACT: In this study authors aimed to investigate the barriers to participation of a sample of Jamaican women in mammography screening. The data were obtained from a previous survey that was conducted in Jamaica from June to August 2013 in the four parishes (Hanover, St. James, Trelawny, and Westmoreland) served by the Western Regional Health Authority (WRHA). WRHA served four hospitals, five non-randomized health centers, and five sites of community events. The sample consisted of women ranging in age between 35 and 83 years, with the mean age of 50.2 (SD = 10.6). The authors used a logistic regression to determine the extent to which variables were associated with breast cancer screening. The level of significace was 0.1 for the bivariate and multivariable analysis. The main factors associated with the lack of breast cancer screening among the women were: being less than 50 years old, single, never thought about breast cancer screening, in need of childcare, and having more than three children. We identified significant barriers to participation in mammography screening experienced by a sample of Jamaican women. Our results suggest that it is necessary to increase the awareness of the importance of breast screening importance among the women who may never have thought about mammography.